(untitled) (Medical Forum Monthly, 2023)
Objective: To compare antibacterial efficacy between 5.25% NaOCL/17% EDTA and 1.3% NaOCL/MTAD irrigation protocols. Study Design: Comparative and in vitro study Place and Duration of Study: This study was conducted at the Operative Dentistry Department at the Isra Dental College Welfare OPD, ISRA University Hospital from December, 2013 to December, 2014. Materials and Methods: E. Faecalis bacteria was grown for 24hr on Brain Heart Infusion agar. E.faecalis was inoculated in root canals of single canaled decoronated teeth (14mm). Step back preparation was done with MAF of 40 # K File. Between every file change root canals were irrigated in group I with 5.25% NaOCl and the finishing rinse was done with 17% EDTA, in group II between each file change root canals were irrigated with 1.3% NaOCl and the finishing rinse was done with MTAD and in Group III between every file change irrigation of canal was done with 5.25%NaOCl. Bacterial sample was taken with a # 40 paper point. Bacterial Culture was done on sheep blood agar and then colonies were counted on a colony counter. Results: There was difference in the effectiveness of all the three irrigation protocols. It was revealed that mean bacterial count was significantly lower with irrigation protocol 5.25%NaOCl/17%EDTA (i.e. Group I) and irrigation protocol 1.3%NaOCl/MTAD (i.e. Group II) as compared to control group (i.e. Group III=irrigation protocol with 5.25%NaOCl). Conclusion: 5.25%NaOCl/17%EDTA showed similar antibacterial efficacy to that of 1.3%NaOCl/MTAD against E. faecalis.